Quantifying maxillary development in chimpanzees and humans: An analysis of prognathism and orthognathism at the morphological and microscopic scales. Issue 157 (August 2021) - Schuh, Alexandra; Gunz, Philipp; Kupczik, Kornelius; Hublin, Jean-Jacques; Freidline, Sarah E.
Abstract: Facial orientation (projection and degree of prognathism) and form in hominins is highly variable, likely related to evolutionary modifications of the microscopic process of bone modeling (the simultaneous cellular activities of bone formation and resorption) during ontogeny. However, in anteriorly projected faces such as those of early hominins, little is known about the link between bone modeling and facial developmental patterns. Similarly, these aspects have been infrequently investigated in extant great apes. In this study, quantitative methods were applied to a cross-sectional ontogenetic sample of 33 chimpanzees ( Pan troglodytes verus ) and 59 modern humans ( Homo sapiens ) to compare the development of maxillary prognathism to orthognathism at both microscopic and macroscopic (or morphological) scales using surface histology and geometric morphometric techniques. Chimpanzees express on average lower amounts of bone resorption than humans on the maxillary periosteum throughout ontogeny; however, the premaxilla is consistently resorbed from early stages on. The presence of bone resorption in the chimpanzee premaxilla, such as that seen in some early hominins, suggests a more ape-like pattern of maxillary bone modeling in these specimens. However, this shows that similarities in bone modeling patterns can lead to variations in shape, suggesting that other aspects of facial growth (such as modifications of rates and timings of development, as well as sutural growth) also played a crucial role in facial evolution. Highlights: Chimpanzees express lower amounts of bone resorption than humans. Bone resorption varies differently in the two species. Bone resorption is found in the chimpanzee premaxilla from birth on. The location of resorption in Pan and Paranthropus suggests an ape-like maxillary bone modeling pattern in early hominins.